Progressive Initiatives for Work Culture Transformation Towards Sustainable Equality in Indonesia - Apriyanto, Apriyanto; Wahdiniawati, Siti Annisa; Faizal, Faizal; Adiazmil, Aan (Westscience Press, 2025)
This qualitative study explores progressive initiatives aimed at transforming work culture to achieve sustainable equality in Indonesia. In-depth interviews were conducted with five key informants, including HR managers, a diversity and inclusion officer, a senior executive, and an organizational development consultant. The findings reveal that successful transformation relies on leadership commitment, employee participation, clear policy development, and continuous education programs. Challenges such as resistance to change, limited awareness of equality principles, and resource constraints were identified, highlighting the need for contextually adapted strategies. The study provides practical insights for organizations seeking to embed equality into their work culture and contributes to the broader understanding of sustainable equality practices in Indonesian workplaces.